2008
DOI: 10.1210/jc.2008-0817
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Reporting of Randomized Controlled Trials in General Endocrinology Literature

Abstract: The quality of RCT reporting in general endocrine literature is suboptimal. We discuss our results, highlight the areas where improvements are needed, and provide some recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 36 publications
8
81
3
Order By: Relevance
“…An overall quality score was calculated based on the sum of 15 selected items [18]. This score has been previously utilized in multiple studies to assess the quality of reporting and has been found to have high inter-rater reliability [29,37].…”
Section: Randomized Controlled Trial Reportingmentioning
confidence: 99%
“…An overall quality score was calculated based on the sum of 15 selected items [18]. This score has been previously utilized in multiple studies to assess the quality of reporting and has been found to have high inter-rater reliability [29,37].…”
Section: Randomized Controlled Trial Reportingmentioning
confidence: 99%
“…We and others have identified deficiencies in the reporting of RCT results. Among them, one of the most common deficiencies is the lack of reporting of key statistical parameters, such as the sample size calculation [1][2][3][4][5], the method in determining random allocation, the use of blinding, and the method of allocation concealment [5].…”
Section: Introductionmentioning
confidence: 99%
“…An association between industry funding and better reporting quality has been reported by some authors. 23,27,28 Whether industry sponsoring is associated with better trial quality or whether the better reporting quality of RCTs achieved as a result of industry funding outweighs the publication bias associated with industry sponsoring remains an interesting subject that is beyond the scope of our study and requires further exploration. In this study, more trials in the new group were endovascular related.…”
Section: Discussionmentioning
confidence: 96%